(untitled) - Uchida, Yoshiko (New York, 1991)
The Invisible Thread is an autobiography written by Yoshiko Uchida. The book is a memoir of her childhood during World War II. It especially tells of her confinement in internment camps across America. It is typical of Yoshiko Uchida's writing, because it tells about being Japanese-American, and always wishing she looked like her white American friends.
Keywords: Tác giả Yoshiko Uchida; Văn học về người chưa thành niên